Experimental and numerical buckling analysis of thin stiffened GFRPs with arbitrarily located stiffeners. Issue 4 (3rd April 2023) - Rafiee, Mojtaba; Amoushahi, Hossein; Hejazi, Mehrdad
Abstract: The Finite Strip Method (FSM) was employed to study the buckling behavior of laminated glass fiber-reinforced polymer (GFRP) stiffened plates with different boundary conditions under axial compression. The theoretical formulation was established based on the first-order shear deformation theory (FSDT) for the thin plate and the stiffener. In this formulation, the stiffeners are not required to be placed on the nodal lines. This feature is considered useful in modeling the stiffened plates in which the stiffener elements are placed arbitrarily in complex planforms. Experimental, numerical and analytical studies were conducted to investigate the effects of the plate width-to-thickness ratio, the stiffener thickness-to-width ratio, dimensions, angle, eccentricity, torsional stiffness and geometric configuration of stiffeners on axial buckling capacity. Furthermore, the obtained results of the analytical method were compared with experimental results and ANSYS code to show its accuracy and convergence. The advantages of the present are that number of elements is much less and the mesh refinement process is much more convenient than commercial finite element software and traditional finite element method (FEM). Therefore, time consumed for analysis is less than the codes which work based on the finite element method.